2011
DOI: 10.1128/aem.02260-10
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Resistance Determinants of German Staphylococcus aureus ST398 Isolates from Nonhuman Sources

Abstract: A series of 100 Staphylococcus aureus isolates ascribed to sequence type 398 (ST398) and recovered from different sources (healthy carrier and diseased pigs, dust from pig farms, milk, and meat) in Germany were investigated for their virulence and antimicrobial resistance genetic background. Antimicrobial resistance was determined by the disk diffusion method. Virulence and resistance determinants (37 and 31 genes, respectively) were tested by PCR. Only two virulence profiles, including the accessory gene regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
113
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(136 citation statements)
references
References 46 publications
19
113
1
3
Order By: Relevance
“…It is capable of acquiring virulence genes, and its acquisition of the PantonValentine leukocidin (PVL) gene (pvl) has been demonstrated [37,61,62]. Regarding other virulence factors, staphylococcal enterotoxins occasionally have been reported in LA-MRSA CC398 in pigs [53,[63][64][65] and turkeys [33••]. In contrast, genes encoding adhesion factors, proteases, hemolysins, other leukocidins, and superantigen-like proteins have been detected frequently in LA-MRSA CC398 isolates from pigs [2•], poultry [26, 33••], and bovines [22].…”
Section: Cc398mentioning
confidence: 99%
“…It is capable of acquiring virulence genes, and its acquisition of the PantonValentine leukocidin (PVL) gene (pvl) has been demonstrated [37,61,62]. Regarding other virulence factors, staphylococcal enterotoxins occasionally have been reported in LA-MRSA CC398 in pigs [53,[63][64][65] and turkeys [33••]. In contrast, genes encoding adhesion factors, proteases, hemolysins, other leukocidins, and superantigen-like proteins have been detected frequently in LA-MRSA CC398 isolates from pigs [2•], poultry [26, 33••], and bovines [22].…”
Section: Cc398mentioning
confidence: 99%
“…Since the first description of the fexA gene in a bovine Staphylococcus lentus isolate (2), this gene has been detected-either as part of the small nonconjugative transposon Tn558 or in combination with the cfr gene in transposition-deficient Tn558 variants-in S. aureus and several coagulase-negative staphylococcal species from healthy and diseased cattle, swine, horses, or humans (3)(4)(5)(6)(7)(8)(9). The fexA gene has also been detected in a Bacillus isolate from swine feces and in environmental pollutants from swine feedlots in China (10,11).…”
mentioning
confidence: 99%
“…Msr(A) and Mef(A) are well known to confer erythromycin resistance in strains of S. aureus [27,95,96,101,102]. The plasmidborne Msr(A) transporter, even though mainly responsible for erythromycin efflux in S. aureus [103], is not present in the strain used in our study, S. aureus ATCC 29213 [104]. Mef(A) is closely related to Mef(B), the erythromycin efflux pump in E. coli P475.10.99.C3 [67], and as pyp decreased the final MIC endpoint for induced cultures of this strain (Figures 3(b) and 3(d)), it can be concluded that Mef(A) is an additional candidate for inhibition by pyp in S. aureus.…”
Section: Discussionmentioning
confidence: 84%